Nicotinamide nucleotide transhydrogenase (NNT) dysfunction impacts on lipid metabolism, and neuromuscular junction (NMJ) in the gastrocnemius muscle of 24-day-old mice - Jingyi Song; Jinmeng Yang; Melissa Bekkenkamp; Claudia Carmone; Jaap Keijer; Sander Grefte (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Performance of TMRM and Mitotrackers in mitochondrial morphofunctional analysis of primary human skin fibroblasts - Shruti Desai; Sander Grefte; Els van de Westerlo; Susette Lauwen; Angela Paters; Jochen H.M. Prehn; Zhuohui Gan; Jaap Keijer; Merel J.W. Adjobo-Hermans; Werner J.H. Koopman (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Normobaric hypoxia shows enhanced FOXO1 signaling in obese mouse gastrocnemius muscle linked to metabolism and muscle structure and neuromuscular innervation - Jingyi Song; Loes P. M. Duivenvoorde; Sander Grefte; Ondrej Kuda; Felipe Martínez-Ramírez; Inge van der Stelt; Dimitra Mastorakou; Evert M. van Schothorst; Jaap Keijer (Pflügers Archiv - European Journal of Physiology, 2023)
Skeletal muscle relies on mitochondria for sustainable ATP production, which may be impacted by reduced oxygen availability (hypoxia). Compared with long-term hypoxia, the mechanistic in vivo response to acute hypoxia remains elusive. Therefore, we aimed to provide an integrated description of the Musculus gastrocnemius response to acute hypoxia. Fasted male C57BL/6JOlaHsd mice, fed a 40en% fat diet for six weeks, were exposed to 12% O 2 normobaric hypoxia or normoxia (20.9% O 2 ) for six hours ( n = 12 per group). Whole-body energy metabolism and the transcriptome response of the M. gastrocnemius were analyzed and confirmed by acylcarnitine determination and Q-PCR. At the whole-body level, six hours of hypoxia reduced energy expenditure, increased blood glucose and tended to decreased the respiratory exchange ratio (RER). Whole-genome transcriptome analysis revealed upregulation of forkhead box-O (FOXO) signalling, including an increased expression of tribbles pseudokinase 3 ( Trib3 ). Trib3 positively correlated with blood glucose levels. Upregulated carnitine palmitoyltransferase 1A negatively correlated with the RER, but the significantly increased in tissue C14-1, C16-0 and C18-1 acylcarnitines supported that β-oxidation was not regulated. The hypoxia-induced FOXO activation could also be connected to altered gene expression related to fiber-type switching, extracellular matrix remodeling, muscle differentiation and neuromuscular junction denervation. Our results suggest that a six-hour exposure of obese mice to 12% O 2 normobaric hypoxia impacts M. gastrocnemius via FOXO1, initiating alterations that may contribute to muscle remodeling of which denervation is novel and warrants further investigation. The findings support an early role of hypoxia in tissue alterations in hypoxia-associated conditions such as aging and obesity.

Interactions between mitochondrial reactive oxygen species and cellular glucose metabolism - Dania C. Liemburg-Apers; Peter H. G. M. Willems; Werner J. H. Koopman; Sander Grefte (Archives of Toxicology, 2015)